Fighting software piracy in Africa: how do legal origins and IPRs protection channels matter? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
In the current efforts towards harmonizing IPRs regimes in the African continent, this paper provides answers to four key questions relevant in the policy decision making processes. After empirically examining the questions, the following findings are established. (1) In comparison to common law countries, civil law countries inherently have a significant autonomous rate of software piracy; consistent with the 'law and property rights' theory. (2) But for IPRs laws, the other IP protection channels (WIPO treaties, Main IP law and multilateral treaties) reduce the incidence of software piracy. (3) In both short-run and long-term, IPRs protection channels in civil law countries appear to mitigate software piracy more than in common law countries. (4) Formal institutions are instrumental in the fight against software piracy through IPRs protection channels.
Keywords: F42; K42; O34; O38; O57; 330; Software piracy; Intellectual property rights; Panel data; Africa